A empregabilidade de jovens em vulnerabilidade social a partir do modelo bioecológico - Souza, Marcelo Ferreira de (2020)
Given the scenario of economic instability and high unemployment, low employability has been highlighted as a serious social problem and a major concern in developed and developing countries. Employment exclusion generally affects all social classes and the most diverse age groups. However, it is young people who live in a situation of social vulnerability that is most impacted, as they face the greatest difficulties in entering the labor market. Public policies have been implemented, but the problem is far from being resolved or minimized. Because of this situation, the need to contribute to the production of new knowledge was perceived, since, as far as is known, literature has been concentrated in groups of university students and more qualified workers. Therefore, as a research objective, this work seeks to understand how individual and contextual characteristics influence the employability and future expectations of young people who live in a situation of social vulnerability. To understand this phenomenon, this work brings to light the Bioecological Model of Human Development. The Model understands that human development arises from proximal processes, that is, from the relationship between individual characteristics, context conditions and temporality. Based on the research question and based on the theoretical framework, the Vila Maria da Conceição community, located in the Partenon neighborhood in Porto Alegre, was chosen as the field of study. The territory that has a reality of extreme social vulnerability, low income per capita, violence, drug trafficking and internalization of other types of vulnerabilities that involve the daily lives of young people. For a better understanding of the problem, an exploratory qualitative approach divided into two phases was used. In the first phase, two exploratory focus groups were carried out in order to understand the context and the common characteristics of the young people and to create the necessary subsidies for the script of the individual interviews. In the second phase, interviews were conducted with young people and with specialists who work or worked directly with young people in the community. As one of the results, it was possible to understand how much the individual characteristics and the context of social vulnerability have a negative influence on the employability and expectations of the future of young people. In order to contribute to a better understanding of this social phenomenon, a “web” of questions was elaborated that could help in understanding those of the individual characteristics of young people, in addition to a schematic model that contemplates the processes necessary for the human and professional development of young people living in socially vulnerable situations.